"Integrated diagnosis" of pilocytic astrocytoma: Molecular diagnostic procedure for an unusual case. Issue 12 (12th November 2018) - Ishida, Yusuke; Tsuda, Masumi; Sawamura, Yutaka; Fujii, Kyoko; Murai, Hiroshi; Horiuchi, Naruyoshi; Orba, Yasuko; Sawa, Hirofumi; Hall, William W; Nagashima, Kazuo; Tanaka, Shinya
Abstract : A 24 year‐old female presented with a mass lesion in the right temporal lobe. This case was difficult to diagnose using histological and immunological methods and therefore molecular analyses were applied to provide a definitive diagnosis. The tumor was well‐demarcated, partially cystic, and irregularly‐enhanced on gadolinium‐enhanced T1‐weighted magnetic resonance images. Pathologically, a large part of the tumor consisted of cells with fine cytoplasmic processes on a myxoid and mucinous background. Cells formed a microcystic structure around the mucinous tissue. Numerous eosinophilic granular bodies, but not Rosenthal fibers, were present. The solid and compact regions of the tumor were composed of fasciculation of dense fibrous glial tissues and occasional multinucleated giant cells. Tumor cells and their fragmented cytoplasmic processes were positively stained with GFAP, while eosinophilic granular bodies were both positive and negative. Xanthomatous changes were not detected and the reticulin fibers were restricted to vascular tissues. The MIB1 index was scored as approximately 10%. In molecular analyses of BRAF, the KIAA1549‐BRAF (K16‐B9) fusion gene was detected in all tumor regions, whereas BRAF V600E mutation was not detected by either conventional Sanger sequencing or the Eprobe‐PCR method. Based on the results of the molecular analyses, this case was diagnosed as pilocytic astrocytoma.